A systematic review and meta-analysis of correlation between cough variant asthma and mycoplasma pneumonia in children - Luyan Jiao; Guoqing Zhang; Yi Yuan; Ling Cao (Archives of Medical Science)
Introduction The aim of the present study was to explore the correlation between cough variant asthma (CVA) and repeated episodes of mycoplasma pneumonia in children.